2020
DOI: 10.3390/pharmacy8010014
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Clinical Pharmacist in an Irish University Teaching Hospital: A Mixed-Methods Study

Abstract: Medication review (MR) is a vital part of the pharmacist’s role in hospital. However, in the South Infirmary Victoria University Hospital (SIVUH), Cork, Ireland, this has not been fully implemented due to resource issues. In addition, the cost of providing this service has not been evaluated. Moreover, it is not clear how other members of the multidisciplinary team e.g., Nurses, value any interventions made as a result of the MR. This mixed methods study assessed the impact of MR in terms of (i) potential clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 44 publications
7
24
1
Order By: Relevance
“…In contrast to our design, these studies focused on specific wards. Our detection rate of pDRPs and the most frequently given recommendations are also in line with previous studies on hospital-wide integration of clinical pharmacists in other hospitals worldwide [ 11 , 12 , 25 – 27 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast to our design, these studies focused on specific wards. Our detection rate of pDRPs and the most frequently given recommendations are also in line with previous studies on hospital-wide integration of clinical pharmacists in other hospitals worldwide [ 11 , 12 , 25 – 27 ].…”
Section: Discussionsupporting
confidence: 89%
“…The high amount of administrative prescribing errors in our study might indicate that physicians need more training for adequate prescribing skills, or that the prescribing system might not work intuitively to prevent this type of error. Poor prescribing practice was also found by Ronan et al [11], where administrative prescribing errors accounted for 15% of the DRPs.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Many studies have shown the effectiveness of the presence of a pharmacist or a clinical pharmacist in hospitals using a computer system to request medication for reducing medication errors and hospital costs [20][21][22][23][24][25]. The findings of one study demonstrated the effectiveness of the presence of a clinical pharmacist in reducing medication errors when using a computer system [26].…”
Section: Discussionmentioning
confidence: 99%
“…Physicians and pharmacists are being progressively encouraged to implement a collaborative method to delivery of health services and the patient care. Strong collaboration between pharmacists and physicians optimizes patient outcomes [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%